Cree Infant Care Practices and Sudden Infant Death Syndrome - Wilson, C. Elizabeth (Can J Public Health, 2000)
Objective: To identify contemporary Cree infant care practices and any risk factors associated with Sudden Infant Death Syndrome. Methods: A questionnaire conducted and recorded in the homes of 70 Cree women (83% of sample available) with infants under 12 months of age, living full time on a Cree reserve. Participatory observation was also used with mothers who agreed to demonstrate certain features of Cree infant care. Findings: 70% of mothers initiated breastfeeding and 43% nursed from 6 to 15 months. Cree infants are tightly swaddled and placed in a supine position for sleeping. Prenatal care is seldom utilized because of cultural beliefs that planning ahead constitutes bad luck during birth or results in deformed infants. Conclusions: Existing infant care practices include several that are considered protective to an infant in terms of reducing vulnerability to SIDS. Swaddling infants in very warm houses and smoking during pregnancy could contribute to a higher SIDS incidence.